2020
DOI: 10.1177/2055116920930181
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic lateral ventricular cystic lesion in a young cat

Abstract: Case summary A 1.5-year-old male neutered Persian cat was referred for acute deterioration of chronic left head tilt and ataxia. A lateral intraventricular cystic lesion, closely associated with the left choroid plexus, was identified on MRI. The intralesional signal intensity and cytological analysis of the fluid revealed a liquid similar to cerebrospinal fluid. After trepanation, an endoscopic-assisted fenestration and aspiration of the cyst were performed to temporally relieve the high intracranial pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Our literature review found only one previously reported case of an intraventricular cyst in the lateral ventricle in a cat by Debreuque et al, 9 who reported a symptomatic presumed choroid plexus cyst in the lateral ventricle. However, histopathological and immunohistochemical examinations were not performed, and it therefore remains uncertain if this lesion truly represented a choroid plexus cyst.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Our literature review found only one previously reported case of an intraventricular cyst in the lateral ventricle in a cat by Debreuque et al, 9 who reported a symptomatic presumed choroid plexus cyst in the lateral ventricle. However, histopathological and immunohistochemical examinations were not performed, and it therefore remains uncertain if this lesion truly represented a choroid plexus cyst.…”
Section: Discussionmentioning
confidence: 79%
“…They have similar intensity to CSF, the cyst wall is visible in T1w MR images but not on CT images, and the cyst wall is easily detected even although the cyst wall is very thin and closely applied to the ventricular lining. 5,6,8 Our literature review found only one previously reported case of an intraventricular cyst in the lateral ventricle in a cat by Debreuque et al, 9 who reported a symptomatic presumed choroid plexus cyst in the lateral ventricle. However, histopathological and immunohistochemical examinations were not performed, and it therefore remains uncertain if this lesion truly represented a choroid plexus cyst.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations